Erythema elevatum diutinum in association with IgA monoclonal gammopathy: A rare case report - Guru Prasad Patnala; Anila P Sunandini; Rama Rayavarapu; Padmasri Somala Yandapalli (Wolters Kluwer Medknow Publications, 2016)
Erythema elevatum diutinum (EED) is a rare form of vasculitis characterized clinically by red-violet brown papules, plaques, and nodules mainly involving the extensor surfaces; histologically by leukocytoclastic vasculitis in early lesions, and fibrosis and cholesterolosis in late lesions. EED has been associated with many systemic disorders including infections, autoimmune disorders, and both benign and malignant hematological disorders. As it is a rare form of vasculitis and only 250 cases reported till date, we report a case of EED in association with IgA monoclonal gammopathy with partial response to dapsone treatment.